'They try to avoid.' How do parents' feelings about ethnicised and classed differences shape gentrifying school communities?. (November 2017) - Vincent, Eve; Butler, Rose; Ho, Christina
Abstract: This article reports on interview-based research into the everyday consequences of gentrification as seen through the prism of local public primary schools in inner Sydney, Australia. We explore the feelings involved in negotiating relations across ethnicised and classed differences within four school communities. Common though contradictory themes across the interviews include: the positive worth accorded to contact with ethnicised difference among white parents; the avoidance of interpersonal contact across ethnicised and classed differences; and the positive worth accorded to classed sameness. Our research finds that the feelings that attend to these themes—discomfort and comfort, desire and disdain—play a significant role in shaping everyday school communities and relationships between parents. We examine the ways in which white parents' desires for social contact with ethnicised others are frequently disappointed and note the disdain and discomfort involved in negotiating contact with classed others. We conclude with a case study involving a complex mix of the themes and feelings listed above: parental engagement with the schools' Parents and Citizens Associations (P&Cs). We argue that P&Cs constitute social spaces dominated by parents with a class-based disposition towards entitlement and authority, from which ethnicised and classed others frequently feel excluded. Highlights: Negotiating difference within multicultural school communities generate hard-to-manage feelings. White parents' desires for contact with difference are hard to realise. Multicultural school communities' P&Cs are often dominated by parents embodying a class-based disposition towards entitlement.